Association between 35 blood and urine biomarkers and oral leukoplakia: a two-sample Mendelian randomization study - Ouyang, Yu-long; Wei, Jing; Liu, Mei-yan; Zhang, Yi; Liu, Sheng-hui; Feng, Hong-chao (Frontiers in Oncology, 2024)
Background Several existing studies have shown a correlation between some of the blood and urine biomarkers and oral leukoplakia (OLK). However, the causality of this relationship remains uncertain. Thus, this study aimed to examine the causal association between 35 blood and urine biomarkers and OLK. Methods Single nucleotide polymorphisms (SNPs) associated with 35 blood and urine biomarkers were selected as instrumental variables (IVs) using a two-sample Mendelian randomization(MR) study to assess the causal relationship between the biomarkers and the risk of oral leukoplakia. We used the inverse variance weighted (IVW) method as the main analysis. Furthermore, several sensitivity analyses were performed to assess heterogeneity, horizontal pleiotropy, and stability. Results Based on the selection criteria of the Inverse Variance Weighted (IVW) method, the analysis found that 5 blood and urine biomarkers were significantly associated with the development of leukoplakia, of which the results of IVW showed that abnormalities of Apolipoprotein B (Apo B), Cholesterol, Low-density Lipoprotein (LDL), Triglycerides (TG) promoted the development of oral leukoplakia, and Non Albumin Protein (NAP) had a protective effect on the development of oral leukoplakia. We then performed a Bonferroni correction for these results, and after correction Apo B was still causally associated with the development of oral leukoplakia (IVW P<0.0007), whereas the other four biomarkers could only provide some evidence of predisposition. Conclusion Our two-sample Mendelian randomization study supports the existence of a causal relationship between these five blood and urine biomarkers and the occurrence of oral leukoplakia, and provides evidence for a number of risk and protective factors for the development of oral leukoplakia; however, the definitive mechanisms for the occurrence and development of oral leukoplakia still remain to be elucidated, and further studies on these relevant mechanisms are still needed.